2018
DOI: 10.7150/ijms.26450
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Immunity To Enterovirus 71 Infection In Humans And Implications For Vaccine Development

Abstract: Enterovirus 71 (EV-A71) is one of the major pathogens causing hand, foot and mouth disease (HFMD). Some strains can lead to neurological disease and fatality in children. Up to date, there is no FDA-approved vaccine to prevent severe HFMD and mortality. Although the inactivated vaccine has advanced to production in China, lack of long-term protection and the requirement of multiple boosters have necessitated the development of other types of vaccines. Recent studies indicate that cellular and not humoral immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Viruses encode proteins that may interfere with the expression of MHC class II antigens by negatively regulating their transcription and/or disrupting their normal cell trafficking, interfering with their presentation to naive CD4+ T cells by disrupting the interaction between MHC class II antigens and TCRs. This is what occurs with the human immunodeficiency virus (HIV) proteins Tat and Nef, as described in more detail throughout this review (Cao et al, 2018; Rivino, 2018; Yee & Poh, 2018).…”
Section: Introductionmentioning
confidence: 79%
“…Viruses encode proteins that may interfere with the expression of MHC class II antigens by negatively regulating their transcription and/or disrupting their normal cell trafficking, interfering with their presentation to naive CD4+ T cells by disrupting the interaction between MHC class II antigens and TCRs. This is what occurs with the human immunodeficiency virus (HIV) proteins Tat and Nef, as described in more detail throughout this review (Cao et al, 2018; Rivino, 2018; Yee & Poh, 2018).…”
Section: Introductionmentioning
confidence: 79%
“…challenge groups ( Figure 6 ). It has been reported that high levels of cytokines such as IL-1β, IL-6, IL-10, and IFN-γ are correlated with clinical severity in patients with pulmonary oedema and encephalitis [ 52 , 53 ], indicating that the immune response of the hSCARB2 mouse model was similar to that of humans. Vaccination prevented the increase in the expression of these cytokines, keeping them at normal levels, indicating that these cytokine responses might be directly related to vaccine-induced immunity.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Genetic variations. There may be intrinsic differences between individuals in countering a viral invasion due to inherited variations in host factors that determine viral susceptibility at the cellular and organismal levels (Yee and Poh 2018).…”
Section: Host Immune Responses To Natural Infection Of Hfmd-related Vmentioning
confidence: 99%
“…(3) Genetic variations. There may be intrinsic differences between individuals in countering a viral invasion due to inherited variations in host factors that determine viral susceptibility at the cellular and organismal levels (Yee and Poh 2018 ). Among the three abovementioned factors, the cellular immune response is the most feasible target for vaccine-based prevention.…”
Section: Host Immune Responses To Natural Infection Of Hfmd-related Vmentioning
confidence: 99%